PENGARUH PEMAHAMAN AKUNTANSI,PEMANFAATAN SISTEM INFORMASI AKUNTANSI, DAN SISTEM PENGENDALIAN INTERNAL TERHADAP KUALITAS LAPORAN KEUANGAN PADA OPD (ORGANISASI PERANGKAT DAERAH) KABUPATEN KARANGASEM - I Gede Agus Wiratama; Rai Dwi Andayani W (UNHI Press, 2022)
Financial statements are a tool for accountability for the company's financial performance. The quality of financial statements must meet the value of the relevant characteristics, and can be compared and can be reached. The purpose of thisstudy wastotest the understanding of Accounting, Utilization of Accounting Information Systems, and Internal Control Systems on the Quality of Financial Reports in OPD (Regional Organizational Organizations) Karangasem Regency. This study uses purposive sampling method to determine the sample. The sample in this study were employees who were involved in financial administration at 39 OPD Karangasem Regency Government as many as 156 respondents, with the data collection method using a questionnaire. Multiple linear regression test was used as a data analysis technique. And analyzed using SPSS softwareThe results showed that the influence of understanding, utilization of accountinginformation systems, and internal control systems significantly affected the quality of financial reports in OPD (Regional Apparatus Organizations) in Karangasem Regency